ANALYSIS AND DESIGN OF HUMAN RESOURCES INFORMATION SYSTEM (SISDM) AT THE OFFICE OF THE ELECTION SUPERVISORY AGENCY OF SOUTH SULAWESI PROVINCE - Abdul Mutalib; Muh. Nur Rasyid; Hery Haryadi Hafid (Jurnal Ilmu Manajemen Profitability, 2022)
The purpose of this research is to find out about the design of human resource information systems in bawaslu of south sulawesi province. This type of qualitative research uses observation and interview data collection techniques. The data analysis technique is data reduction. The results showed that the analysis of employee training needs serves to classify what types of training are needed by employees in an institution. Given the one hand bawaslu which has a wide scope of work, namely in the south sulawesi province area, it has many employees who work and must understand different knowledge and skills by facing a place of supervision which also consists of various characteristics of people. With the HR design, it can provide convenience in the process of calculating employee performance and assist the HR departement in evaluating the performance of employees within the organization as well as employee transfer statistics